Effect of dental varnishes in prevention of enamel demineralization adjacent to orthodontic brackets - Eby Varghese; Renu S Samson; Ashley Thomas; George Sam; Sadananda Hota; Nivedita Sahoo (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of the current research was to assess the ability of different dental varnishes in averting enamel demineralization adjoining the orthodontic brackets. Materials and Methods: Seventy-five premolars devoid of dental caries that were subjected to extraction for orthodontic purposes were employed in this research. The surface of enamel was etched with 37% phosphoric acid and subjected to primer application. Individual brackets were placed on the midregion of the buccal surfaces of the premolars with Transbond™ XT adhesive. Postbracket bonding, the dry premolar tooth samples were set aside cautiously. The samples were then allocated to three groups: Group I: Duraphat Varnish, Group II: Clinpro XT Varnish, and Group III: Profluorid Varnish. Every sample was independently subjected to immersion in demineralizing solution for a period of 96 h at 37°C in an incubator. Areas of demineralization were evaluated by documenting the microhardness along the severed surface using a microhardness tester equipped with a Vickers diamond. Results: The highest surface microhardness was noted with Profluorid Varnish group at 328.48 ± 1.12 in pursuit by Clinpro XT Varnish group at 322.08 ± 0.04 as well as Duraphat Varnish group at 307.42 ± 0.28 with a statistically noteworthy dissimilarity amid the groups. Conclusion: In conclusion, the three varnishes employed had an influence on the prevention of enamel demineralization surrounding the orthodontic brackets. Profluorid varnish however exhibited maximum efficiency in avoiding enamel demineralization versus Clinpro XT varnish as well as Duraphat varnish group.